Weed pressure and turfgrass establishment in response to mulching media. (11th December 2020) - Henry, Gerald; Hoyle, Jared
Abstract: Turfgrass establishment on the Texas High Plains is often compromised by wind desiccation, high temperatures, and reduced water inputs. Application of cotton gin trash at seeding may help increase germination through buffering and insulation. Therefore, field experiments were conducted to examine weed pressure and establishment of 'Sahara' common bermudagrass [ Cynodon dactylon (L.) Pers.] and 'Bowie' buffalograss [ Bouteloua dactyloides (Nutt.) J.T. Columbus] in response to cotton gin trash and industry standards (hydro‐mulch and wheat [ Triticum aestivum L.] straw) used as mulching media. The greatest amount of common bermudagrass cover 12 wk after planting (WAP) was observed in response to hydro‐mulch (89%) and no mulch (85%), while wheat straw and gin trash mulch only resulted in 70 and 60% cover, respectively. The greatest amount of buffalograss cover 12 WAP was observed in response to hydro‐mulch (55%). All other treatments resulted in ≤20% buffalograss cover 12 WAP. Weed cover in bermudagrass 12 WAP was highest in response to gin trash (33%) followed by (fb) wheat straw (24%) fb no mulch (12%) and hydro‐mulch (10%). Weed cover in buffalograss 12 WAP was highest in response to wheat straw (72%) fb gin trash (52%) fb no mulch (36%) fb hydro‐mulch (22%). Utilization of gin trash as mulch only resulted in 60% bermudagrass cover and 20% buffalograss cover, while weed pressure was 33–52% cover. Further refinement of gin trash may improve use as a mulch through the reduction of weed seed and removal of cotton plant fragments that limit light infiltration to the soil surface.